The roots of modern conservatism : Dewey, Taft, and the battle for the soul of the Republican Party - Bowen, Michael (Michael D.) (University of North Carolina Press, 2011)
Initially, Bowen argues, the separate Dewey and Taft factions endorsed fairly traditional Republican policies. However, as their conflict deepened, the normally mundane issues of political factions, such as patronage and fund-raising, were overshadowed by the question of what "true" Republicanism meant. Taft emerged as the more conservative of the two leaders, while Dewey viewed Taft's policies as outdated. Eventually, conservatives within the GOP organized against Dewey's leadership and, emboldened by the election of Dwight Eisenhower, transformed the party into a vehicle for the Right.